Pilot physiology, cognition and flight performance during flight simulation exposed to a 3810-m hypoxic condition. Issue 1 (2nd January 2017) - Peacock, Corey A.; Weber, Raymond; Sanders, Gabriel J.; Seo, Yongsuk; Kean, David; Pollock, Brandon S.; Burns, Keith J.; Cain, Mark; LaScola, Phillip; Glickman, Ellen L.
Abstract : Background. Hypoxia is a physiological state defined as a reduction in the distribution of oxygen to the tissues of the body. It has been considered a major factor in aviation safety worldwide because of its potential for pilot disorientation. Pilots are able to operate aircrafts up to 3810 m without the use of supplemental oxygen and may exhibit symptoms associated with hypoxia. Objective . To determine the effects of 3810 m on physiology, cognition and performance in pilots during a flight simulation. Methods . Ten healthy male pilots engaged in a counterbalanced experimental protocol comparing a 0-m normoxic condition (NORM) with a 3810-m hypoxic condition (HYP) on pilot physiology, cognition and flight performance. Results . Repeated-measures analysis of variance demonstrated a significant ( p ≤ 0.05) time by condition interaction for physiological and cognitive alterations during HYP. A paired-samples t test demonstrated no differences in pilot performance ( p ≥ 0.05) between conditions. Conclusion . Pilots exhibited physiological and cognitive impairments; however, pilot performance was not affected by HYP.